A Change in Practice Protocol: Preformed Metal Crowns for Treating Non-Infected Carious Primary Molars in a General Practice Setting – A Service Evaluation. Issue 4 (December 2015) - Taylor, Greig D
Restoring non-infected carious primary molars can pose a challenge to the general dental practitioner. This paper aims to assess the effect on primary caries management and patient experience in a general dental practice setting, when restoring non-infected carious primary molars using a Hall preformed metal crown (PMC).